Impactful times : memories of 60 years of shock wave research at Sandia National Laboratories /: memories of 60 years of shock wave research at Sandia National Laboratories. (2017) - Asay, J. R; Chhabildas, L. C (Lalit C.); Lawrence, R. Jeffery; Sweeney, Mary Ann
No abstract available